中国商业银行信货风险管理 ：信货评分模型的应用 = Credit risk management of commercial banks in China : an application of credit-scoring model - 陈颐 Chen, Yi (2008)
According to the analysis of credit risk management of Chinese and international banking industry, the dissertation focuses on establishing a credit-scoring model widely used in the western banks to evaluate the credit risk of consumer lending and small-business loans. Based on the sample of 1000 business loans of Nanjing, using the regression way of Logit Model, the credit-scoring model is oriented to small and medium business borrowers operated in Nanjing of China. From this model, we conclude the relationship between the probability of predicting a loan performed well and the useful independent variables, that is, five determinative factors including profit, debt ratio, total assets, sales and the type of business (state business or non-state business). Developing and analysis of the model not only teach us the method of how to establish a logit model, but also or more importantly strengthen our knowledge on the current situation and problems of the credit risk management in China's commercial banks. Just due to such understand and attention, we establish this model and expect it be helpful to choose the true factors determining the credit risk evaluation under the specific environment in which the banks and businesses cooperate, and wish it can be dedicated to improve the efficiency and performance of credit risk management in China's commercial banks.